An Exploratory Study of Corporate Social Responsibility in Electric Utility Sector. A Comparison between TNB, Malaysia And CLP, Hong Kong - Sigh, Jasbinder (2006)
I begin with Adam Smith’s “invisible hand” where each individual strives for his own goal resulting in efficient distribution of the resources and wealth1. In line with this Milton Freidman (1970) has argued that business social responsibility is to maximise profit for the shareholder and failure to do so is being irresponsible which leads to misallocation of scarce resources. This is also supported by company law, which stresses that the board responsibility is to ensure profitability for the shareholder.